Modulatory effects of dietary vitamin E on bisphenol A toxicity in male Oreochromis niloticus: insights into oxidative stress, hepatic dysfunction, reproductive hormone and histological alterations - Abhilipsa Biswal; Prem Prakash Srivastava; Kedar Nath Mohanta; Subodh Gupta; Prem Kumar; Tincy Varghese; Manish Jayant; Annam Pavan Kumar (Journal of Fisheries, 2026)
The effectiveness of graded dietary vitamin E levels in alleviating bisphenol A (BPA) induced oxidative stress, hepatic dysfunction, reproductive hormone disruption and histological alterations in male Oreochromis niloticus was tested through a 45-day study using seven experimental groups: a negative control (C1; no BPA exposure; basal dose of 100 mg vitamin E kg–1 diet), a positive control (C2; exposed to 0.04 ppm BPA; basal dose of 100 mg vitamin E kg–1 diet), and five treatment groups: T1 (0.04 ppm BPA; 200 mg  vitamin E kg–1 diet), T2 (0.04 ppm BPA; 400 mg vitamin E kg–1 diet), T3 (0.04 ppm BPA; 600 mg vitamin E kg–1 diet), T4 (0.04 ppm BPA; 800 mg dietary vitamin E kg–1 diet), and T5 (0.04 ppm BPA; 1000 mg vitamin E kg–1 diet). Exposure to BPA resulted in haematological and antioxidant enzymes alterations with increased superoxide dismutase and catalase activities. Further, a decrease in 11-ketotestosterone and increase in estradiol levels was observed, which corresponded with pronounced histopathological damage in testicular tissue, including degeneration of seminiferous tubules and disrupted spermatogenesis. The dietary incorporation of 600 mg vitamin E kg–1 diet produced most consistent improvement across physiological and endocrine parameters, along with near-normal testicular architecture in T3 group. Collectively, the findings demonstrate that dietary vitamin E effectively mitigates BPA-induced toxicity within an optimal range, emphasizing the importance of dose optimization for maintaining reproductive health in O. niloticus.